2014
DOI: 10.1182/blood-2014-06-582775
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical PAR3 activation by factor Xa identifies a novel pathway for Tie2 activation and stabilization of vascular integrity

Abstract: • Factor Xa activates PAR3 in the presence of EPCR by noncanonical cleavage at Arg41.• Noncanonical PAR3 activation induces Tie2 activation, upregulation and redistribution of ZO-1, and stabilization of tight junctions.Endothelial barrier protective effects of activated protein C (APC) require the endothelial protein C receptor (EPCR), protease-activated receptor (PAR) 1, and PAR3. In contrast, PAR1 and PAR3 activation by thrombin results in barrier disruption. Noncanonical PAR1 and PAR3 activation by APC vs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…PAR1 and PAR3 heterodimerize on endothelial cells to help explain thrombin-mediated signaling (55). Thus far, it has been shown that thrombin, APC, and FXa can cleave PAR3 (24,53,56,57). APC-mediated cytoprotective signaling on neuronal cells, podocytes, and endothelial cells occurs in part via the activation of PAR3 and requires EPCR (24, 58 -60).…”
Section: Discussionmentioning
confidence: 99%
“…PAR1 and PAR3 heterodimerize on endothelial cells to help explain thrombin-mediated signaling (55). Thus far, it has been shown that thrombin, APC, and FXa can cleave PAR3 (24,53,56,57). APC-mediated cytoprotective signaling on neuronal cells, podocytes, and endothelial cells occurs in part via the activation of PAR3 and requires EPCR (24, 58 -60).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EPCR also regulates the specificity of FXa‐induced signaling in cells. In this line, FXa‐induced PAR‐1 activation at canonical Arg41 disrupts endothelial cell barrier integrity, whereas in the presence of EPCR, cleavage of PAR‐3 by FXa at non‐canonical Arg41 enhanced endothelial barrier protective function through phosphorylation of the transmembrane tyrosine kinase receptor, Tie‐2 (Stavenuiter and Mosnier, ). FXa‐induced Tie‐2 phosphorylation at Ser1119 and Y992 induces up‐regulation of tight junction protein ZO‐1, which is necessary for cell–cell interaction and stabilization of tight junctions between cells (Stavenuiter and Mosnier, ).…”
Section: Signaling Properties Of Fxamentioning
confidence: 99%
“…These complex pathways display significant crosstalk where, for example, EPCR signaling regulates S1P1R activation through PAR-1 15 and Tie2 transactivation through PAR-3 cleavage 16 to maintain barrier function. The maintenance of endothelial integrity ultimately depends on the balance of disruptive and protective pathways.…”
Section: Endothelial Cell Barriersmentioning
confidence: 99%